MARINE INVERTEBRATE-ASSOCIATED BACTERIA IN CORAL REEF ECOSYSTEMS AS A NEW SOURCE OF BIOACTIVE COMPOUNDS - ocky radjasa (JOURNAL OF COASTAL DEVELOPMENT, 2004)
Coral reefs are the most species-rich environments in the oceans. Reefs cover 0.2% of the ocean’s area and yet they provide home to one-third of marine fishes and to tens of thousands of other species. Coral reefs provide essential fish habitat, support endangered and threatened species, and harbor protected marine mammals. Despite the obvious ecological value of these habitats, most coral reefs around the world, including Indonesia’s, are threatened or already being destroyed by human activities. The search for bio-active compounds extracted from coral reef invertebrates which is emerging as an area of increasing interest among biotechnological companies, further threatens the integrity of the reef ecosystem. It would be of great interest to find alternative sources of these compounds, in order to preserve this precious environment and also to obtain higher amounts of these bi-active molecules. Increasing observations suggest that a number of bio-active metabolites obtained from invertebrates are in fact produced by associated microorganisms: this has prompted research into the rapidly expanding field of study of metabolites derived from microorganisms associated with reef invertebrates. The possibility to culture relevant microorganisms in bioreactors would enable the production of large amounts of the bio-molecules of interest, at the same time preserving the marine ecosystem from exploitation.